Law, governance, and management of the Colorado River: fall 2022 schedule - Colorado Water Center, author (Colorado State University. Libraries, 2022)
Climate change, decreasing flows, increasing population and economic uses have challenged Colorado River managers and policymakers. This class will explore the history, law, management and current challenges facing all who depend on the Colorado River.
Interdisciplinary water resources seminar, fall 2022
2022 theme: Law, governance, and management of the Colorado River: reflections on the 100th Anniversary of the signing of the Colorado River Compact.
Title by cataloger.
Keywords: Colorado Water Center. GRAD 592; Colorado River Compact (1922 November 24)